Herpes Simplex Virus Type 1 Enhances Expression of the Synaptic Protein Arc for Its Own Benefit - Acuña-Hinrichsen, Francisca; Muñoz, Mariela; Hott, Melissa; Martin, Carolina; Mancilla, Evelyn; Salazar, Paula; Leyton, Luis; Zambrano, Angara; Concha, Margarita I.; Burgos, Patricia V.; Otth, Carola (Frontiers in Cellular Neuroscience, 2019)
Herpes simplex virus type 1 (HSV-1) is a neurotropic virus able to reach the central nervous system (CNS) after primary infection in oronasal mucosa. HSV-1 establishes latency inside neurons due the repression of its gene expression process that is related with periodic reactivations in response to cellular stress conditions constituting a risk factor for neurodegenerative diseases, including Alzheimer’s Disease. The immediate-early gene Arc plays an essential role in neuronal morphology, synaptic plasticity and memory formation. Arc acts as a hub protein interacting with components of the endocytic machinery required for AMPA receptor recycling as well as with proteins of the post-synaptic density and actin cytoskeleton. However, to date, no studies have evaluated whether persistent neurotropic HSV-1 infection modulates expression and function of Arc protein in brain tissue. Here we report that neuronal in vivo and in vitro infection of HSV-1 significantly increases Arc protein levels showing a robust perinuclear distribution in neuronal cell lines, a process that is dependent on active HSV-1 replicative cycle. Finally, we found that silencing of Arc protein caused a decrease in HSV-1 total proteins and viral progeny suggests that Arc is involved in HSV-1 life cycle. Our studies strongly suggest that pathogenicity of HSV-1 neuronal reactivations in humans could be mediated in part by Arc neuronal up-regulation and its potential role in endocytic trafficking and AMPA-neuronal function impairment. Further studies are necessary to define whether this phenomenon could have repercussions in cognition and learning processes in infected individuals.